KINERJA PELAYANAN PUBLIK DI KANTOR KECAMATAN PULAU HARUKU KABUPATEN MALUKU TENGAH - Dino Latuconsina; Mohamad Arsad Rahawarin; Pieter Sammy Soselisa (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Public service is one of the essential aspects of governance that plays a role in meeting the needsof society. This study aims to analyze the performance of public services in the issuance of electronic IDcards (e-KTP) at the District Office of Pulau Haruku, Central Maluku Regency. This research employs aqualitative descriptive method, utilizing data collection techniques such as observation, interviews, anddocumentation. The findings indicate that public service performance at the Pulau Haruku District Officestill faces several challenges, including limited infrastructure, a lack of skilled technical personnel, and anadministrative system that is not yet optimal. However, efforts to improve services continue throughenhancing staff competencies and providing more transparent information to the public. Based on theresearch findings, it is recommended that the local government allocate a budget for improving serviceinfrastructure, increase training for service personnel, and accelerate the integration of digital systems toenhance efficiency in e-KTP issuance. With these measures, it is expected that the quality of public servicesin Pulau Haruku District can be optimized and meet the expectations of the community